Sistem Informasi penjualan Alat Tulis Kantor (ATK) Pondok Pesantren Al-Falah Yang Efektif Dan Efisien Dengan Menggunakan Php Dan Mysql - Mardani, Alif; Achmad Baijuri; Firman Santoso (Computer Science and Information Technology, 2024)
The rapid development of information technology has permeated various sectors, including cooperatives. Utilizing technology in cooperatives is crucial for enhancing the efficiency and effectiveness of decision-making. This study aims to design an integrated sales management system for ATK Mitra Kopontren Musa'adah. The current manual system has several drawbacks, such as data loss and inaccurate financial reports. By implementing an integrated information system, the cooperative is expected to produce more accurate, timely, and accessible financial reports, thereby improving its performance and transparency.